Modern views on clinical and economical effectiveness of rosuvastatin - S. K. Zyryanov; Yu. B. Belousov (Кардиоваскулярная терапия и профилактика)
Clinical trial and meta-analyis data demonstrate the important role of lipid-lowering therapy in reducing the risk of coronary heart disease (CHD) complications and CHD death. Practitioners need additional information to select from the already available statins the one that is not only effective and safe, but also the most acceptable from the pharmaco-economical point of view. The research data available support high efficacy, good safety profile, and clinic-economical effectiveness of a new synthetic statin - rosuvastatin.